The Utility of Table-Top Exercises in Teaching Nuclear Security - Christopher Hobbs; Luca Lentini; Matthew Moran (International Journal of Nuclear Security, 2016)
In the emerging field of nuclear security, those responsible for education and training are constantly seeking to identify and engage with tools and approaches that provide for a constructive learning environment. In this context, this paper explores the nature and value of Tabletop exercises (TTX) and how they can be applied in the nuclear security context. On the one hand, the paper dissects the key components of the TTX and considers the broader pedagogical benefits of this teaching method. On the other hand, the paper draws lessons from the authors’ experience of running TTXs as part of nuclear security professional development courses (PDCs) over the past six years. The paper finds that the TTX holds enormous benefit as a learning resource when developed as part of a comprehensive approach to nuclear security education.
Keywords: nuclear; security; CBRN; nuclear terrorism; WMD; training; table-top; teaching methods; pedagogy; curriculum design